MRI of the inferior alveolar nerve and lingual nerve—anatomical variation and morphometric benchmark values of nerve diameters in healthy subjects - Burian, Egon; Probst, Florian A.; Weidlich, Dominik; Cornelius, Carl-Peter; Maier, Lisa; Robl, Teresa; Zimmer, Claus; Karampinos, Dimitrios C.; Ritschl, Lucas M.; Probst, Monika (Clinical Oral Investigations, 2020)
Objective Since MRI using dedicated imaging sequences has recently shown promising results in direct visualization of the inferior alveolar nerve (IAN) and the lingual nerve (LN) with high spatial resolution, the aim of this study was to generate suitable standard specifications to reliably depict the IAN and LN in MRI and to delineate the anatomy and its variants of these nerves in healthy subjects. Methods Thirty healthy volunteers were examined on a 3-T scanner (Elition, Philips Healthcare, Best, the Netherlands). The sequence protocol consisted of 3D STIR, 3D DESS, and 3D T1 FFE “black bone” sequences. Results The study reconfirmed a good feasibility of direct visualization of proximal and peripheral portions of the IAN and of the proximal course of the LN. The STIR sequence showed the highest apparent signal to noise ratio (aSNR) and best apparent nerve-muscle contrast to noise ratio (aNMCNR) for IAN and for the LN. The applied MRI sequences allowed to differentiate the tissue composition of the neurovascular bundle inside the mandibular canal. Conclusion Dedicated MRI sequence protocols proved effectively to detect the IAN and LN and their course in healthy volunteers. The tissue composition of the mandibular neurovascular bundle was conclusively distinguishable as was the varying topography inside multiple bony channels. Clinical relevance The presented data on the precise and valid visualization of the IAN and LN have clinical implications in respect to local anesthesia prior to dental treatments in the mandible but also regarding surgical procedures and implant insertion in the molar region.